Molecular simulation study of CO2 and O2 adsorption characteristics and diffusion pattern in coal body at atmospheric pressure - JIA Tinggui; WU Xingyu; QU Guona (矿业科学学报)
In order to investigate the adsorption characteristics and diffusion law of CO2 and O2 in coal, the adsorption and diffusion processes of CO2 and O2 in coal at different molar ratios, temperatures and pressures were simulated using the grand canonical system Monte Carlo and molecular dynamics methods. The findings indicated that: ① CO2 was distributed in clustered aggregation and O2 was distributed in point-like dispersion in coal. Under identical conditions, the adsorption quantity, equivalent adsorption heat, average mass density, and adsorption selectivity were CO2>O2. ② With the increase of the molar ratio of CO2, the adsorption amount, the equivalent adsorption heat, and the diffusion coefficient of CO2 exhibited a tendency to increase. The mass density of CO2 increased with the increase of the mole fraction, but an excessive increase in the mole fraction of CO2 results in an increase in the O2 diffusion coefficient. With increasing pressure, the adsorption selectivity coefficient of CO2 decreases from 7.67 to 3.69. ③ The adsorption of O2 is weaker than that of CO2, and the diffusion of O2 shows a decreasing trend, while the diffusion of CO2 shows an increasing trend. An increase in temperature has a detrimental effect on the adsorption capacity of coal for CO2 and O2. However, the diffusion of O2 and CO2 exerts a significant promotional influence, with a higher temperature facilitating the diffusion of the two gases and accelerating the desorption from coal. Consequently, the diffusion coefficient demonstrates an increasing trend. The findings of this study may serve as a valuable reference for the prevention and control of spontaneous coal combustion and other related disasters.